2009
DOI: 10.1271/bbb.80564
|View full text |Cite
|
Sign up to set email alerts
|

KIBRA Co-Localizes with Protein Kinase Mζ (PKMζ) in the Mouse Hippocampus

Abstract: KIBRA is a WW domain-containing protein that can bind to protein kinase C (PKC ). The SNP of the ninth intron of the KIBRA gene is associated with human episodic memory performance. Protein kinase M (PKM ), a brain-specific variant of PKC , plays important roles in memory formation. Here we examined the interaction of KIBRA and PKM in the adult mouse brain. Immunoprecipitation using newly-raised anti-KIBRA antibody revealed the interaction between KIBRA and PKM in the brain. KIBRA was colocalized with PKM in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 31 publications
0
43
0
Order By: Relevance
“…The KIBRA protein has been linked to memory-related processes through interaction with several postsynaptic proteins involved in synaptic plasticity and induction of long-term potentiation, including dendrin, synaptopodin, and PKC molecules (Büther et al, 2004;Schneider et al, 2010). Yoshihama et al (2009) recently showed, in the mouse hippocampus, that KIBRA colocalizes with PKM, the only known molecule both necessary and sufficient for long-term potentiation maintenance (Sacktor, 2008), and this interaction was suggested as the functional role of KIBRA in memory.…”
Section: Discussionmentioning
confidence: 99%
“…The KIBRA protein has been linked to memory-related processes through interaction with several postsynaptic proteins involved in synaptic plasticity and induction of long-term potentiation, including dendrin, synaptopodin, and PKC molecules (Büther et al, 2004;Schneider et al, 2010). Yoshihama et al (2009) recently showed, in the mouse hippocampus, that KIBRA colocalizes with PKM, the only known molecule both necessary and sufficient for long-term potentiation maintenance (Sacktor, 2008), and this interaction was suggested as the functional role of KIBRA in memory.…”
Section: Discussionmentioning
confidence: 99%
“…KIBRA RNA is expressed in the whole brain with a peak in memory-related structures such as the hippocampus and the temporal lobe (Papassotiropoulos et al, 2006). As a component of the neuronal cytoskeleton, KIBRA might have a role in brain development connecting cytoskeletal and signaling molecules (Johannsen et al, 2008;Yoshihama et al, 2009). KIBRA is also a substrate for protein kinase Cz, which is crucially involved in synaptic plasticity and memory formation (Buther et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The KIBRA protein is discussed to be involved in brain development and memory formation as a postsynaptic scaffold protein connecting cytoskeletal and signaling molecules (Johannsen et al, 2008;Yoshihama et al, 2009). However, results for episodic memory have been inconsistent across studies, ranging from the originally reported beneficial effects of the T-allele on memory functions (Almeida et al, 2008;Papassotiropoulos et al, 2006;Schaper et al, 2008;Yasuda et al, 2010;Vassos et al, 2010) to null findings (Need et al, 2008) and to even poorer memory in T-allele carriers (Nacmias et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It interacts with dynein light chain 1 to activate the oestrogen receptor (Rayala et al 2006) and discoidin domain receptor 1 to modulate collagen-induced signalling (Hilton et al 2008). Recently, protein kinase Mζ, a brain-specifi c variant of PKCζ, was reported to be combined with KIBRA and supposed to modulate molecular pathways of memory formation (Yoshihama et al 2009). …”
Section: Cognitive Testsmentioning
confidence: 99%